2012
DOI: 10.1111/j.1399-3062.2012.00782.x
|View full text |Cite
|
Sign up to set email alerts
|

Renal grafts from anti‐hepatitis B core‐positive donors: a quantitative review of the literature

Abstract: Our review indicates that the risk of HBV transmission from HBcAb-positive kidney donors is extremely low. Therefore, kidneys from these donors can be transplanted safely into ESRD patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
40
0
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 50 publications
(42 citation statements)
references
References 60 publications
1
40
0
1
Order By: Relevance
“…(259,266,267) In a systematic review of studies that included 1,385 kidney recipients with organs from donors that were HBsAg negative but anti-HBc positive, 0.3% became HBsAg positive and 2.3% became anti-HBc positive. (267) The presence of anti-HBc and/or anti-HBs in the recipients is associated with protection against HBV seroconversion. (268) However, to reduce this small risk of HBV infection further, antiviral therapy should be administered to prevent de novo HBV infection.…”
Section: I Nonliver Solid Organ Transplant Recipientsmentioning
confidence: 99%
“…(259,266,267) In a systematic review of studies that included 1,385 kidney recipients with organs from donors that were HBsAg negative but anti-HBc positive, 0.3% became HBsAg positive and 2.3% became anti-HBc positive. (267) The presence of anti-HBc and/or anti-HBs in the recipients is associated with protection against HBV seroconversion. (268) However, to reduce this small risk of HBV infection further, antiviral therapy should be administered to prevent de novo HBV infection.…”
Section: I Nonliver Solid Organ Transplant Recipientsmentioning
confidence: 99%
“…50 In a review of nine studies with 1,385 evalu able HBsAgnegative recipients of kidneys from anti-HBcAg-positive donors, new HBV serologic markers were observed in only 45 (3.2%) patients and the rate of HBsAg acquisition was only 0.28% (four patients) with no evidence of symptomatic hepatitis. 51 This study did not explore the influence of recipient anti-HBsAg status or use of prophylactic therapy. Patient or graft outcomes were not worse among patients with HBsAg acquisition or evidence of anti-HBsAg or anti-HBcAg seroconversion.…”
Section: Viral Infectionsmentioning
confidence: 99%
“…Evidence has shown that in solid organ transplantations such as kidney [42], bone marrow [43], and heart [44], HBV transmission is usually lower than 5%; while for recipients of liver transplants, a variable rate of de novo HBV infection occurs between 17% and 95% depending on the HBV serological markers of the donor [27, 37, 38, 45, 46]. However, the infection status of the recipient is also highly relevant, considering that among 4.4% and 17.6% of OBI has been reported in liver transplant recipients [28, 4749].…”
Section: Introductionmentioning
confidence: 99%